Ensaios em economia ambiental - Carvalho, Patricia Soares De Araújo (2016)
This paper is dedicated to an empirical analysis of topics in Environmental Economics in which the variable of interest is qualitative. Therefore, this paper was divided into three essays. The first essay aimed to investigate the perception of economic agents from their level of interest on environmental concerns regarding the Paraiba River estuary. Applying the econometric ordered logit model, it was verified that the environmental perception of an individual suffers influence from socioeconomic variables, as well as how the agent analyses the effort of the society, companies and other individuals to preserve the environment. The objective of the second essay, using the Contingent Valuation Method (CVM) was to verify the possibility of suggesting a proposal for a Payment for Environmental Services (PES) for the Cabo Branco Park. The confidence interval of the average/median Willingness to Pay (WTP), estimated according to Hahnemann's approach (1984), was determined by Krinsky-Robb's method (1986) and estimated through the application of the logit econometric model, thus allowing the calculation of a WTP individual of R$ 15.16 per visitation. In general, the results of this research suggest that, based on the environmental service provided by the Cabo Branco cliff, the planning of a proposal for a PSA for the Cabo Branco Park is regarded as an important initiative to solve possible problems related to a lack of financial resources for the funding of preservation activities. The objective of the third essay, which also used the Contingent Valuation Method, was to estimate the WTP and to identify the determining factors of (un) certainty in relation to the WTP for residential properties with an environmental certification in the city of João Pessoa (PB). The confidence interval of the average/median WTP (Willingness to Pay), estimated according to Hahnemann's approach (1984), was determined by KrinskyRobb's method (1986) and estimated based on the application of the econometric logit model, thus allowing the calculation of an individual WTP of R$ 23.913,93 per seal (withdrawing the protest votes). Regarding the determining factors of total certainty (over 80%), the estimated econometric results through the application of the ordered logit model, suggest that males with a higher level of education and more interest in environmental issues have a higher level of certainty in relation to paying for an environmental seal in residential real estate. It os perceived from the research results in the city of João Pessoa that a demand for residential real estate with environmental seals exists.